Racial representation in the planning profession in South Africa: Some scenarios - Badenhorst, MS (Acta Structilia, 1999)
The planning profession in South Africa, along with the majority of other institutions dating back to the previous dispensation, is to a large extent dominated by whites. Given the role which planners can play in the reconstruction and development of the country, and concomitant governmental pressure, the profession must become more representative of the country’s population at large. The question is, however, how long it will take to bring about significant changes in the composition of the planners’ corps under specified conditions. In this article various scenarios are examined, based on certain assumptions and on variations in the output of graduates from the various planning schools. The most important conclusion is that the composition of the planning population is not going to change overnight. Neither is there a quick-fix solution to the problem. The exploration indicates that a drastic change in the demographic composition of the planning profession lies beyond the professional lifetime of the majority of white planners of the present generation.